Ferroptosis: an important player in the inflammatory response in diabetic nephropathy - Li, Jialing; Li, Luxin; Zhang, Zhen; Chen, Peijian; Shu, Haiying; Yang, Can; Chu, Yanhui; Liu, Jieting (Frontiers in Immunology, 2023)
Diabetic nephropathy (DN) is a chronic inflammatory disease that affects millions of diabetic patients worldwide.The key to treating of DN is early diagnosis and prevention. Once the patient enters the clinical proteinuria stage, renal damage is difficult to reverse. Therefore, developing early treatment methods is critical. DN pathogenesis results from various factors, among which the immune response and inflammation play major roles. Ferroptosis is a newly discovered type of programmed cell death characterized by iron-dependent lipid peroxidation and excessive ROS production. Recent studies have demonstrated that inflammation activation is closely related to the occurrence and development of ferroptosis. Moreover, hyperglycemia induces iron overload, lipid peroxidation, oxidative stress, inflammation, and renal fibrosis, all of which are related to DN pathogenesis, indicating that ferroptosis plays a key role in the development of DN. Therefore, this review focuses on the regulatory mechanisms of ferroptosis, and the mutual regulatory processes involved in the occurrence and development of DN and inflammation. By discussing and analyzing the relationship between ferroptosis and inflammation in the occurrence and development of DN, we can deepen our understanding of DN pathogenesis and develop new therapeutics targeting ferroptosis or inflammationrelated regulatory mechanisms for patients with DN.